2022
DOI: 10.1089/ten.teb.2021.0036
|View full text |Cite
|
Sign up to set email alerts
|

Resident Macrophages and Their Potential in Cardiac Tissue Engineering

Abstract: Many facets of tissue engineered models aim to understand cellular mechanisms to recapitulate in vivo behavior, study and mimic diseases for drug interventions and to provide better understanding towards improving regenerative medicine. Recent and rapid advances in stem cell biology, material science and engineering, have made the generation of complex engineered tissues much more attainable. One such tissue, human myocardium; is extremely intricate, with a number of different cell types. Recent studies have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…The inflammatory response is thought to be involved in the pathogenesis of MI, coordinating beneficial homeostatic responses in the heart to promote cardiac repair after MI [ 17 ]. The innate immune cells which are recruited into myocardial tissue mediated the clearance of necrotic cardiomyocytes through phagocytosis after MI [ 18 ]. However, DAMPs and ischemia triggered an excessive inflammatory response of infiltrative inflammatory cells, leading to increased myocardial damage.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response is thought to be involved in the pathogenesis of MI, coordinating beneficial homeostatic responses in the heart to promote cardiac repair after MI [ 17 ]. The innate immune cells which are recruited into myocardial tissue mediated the clearance of necrotic cardiomyocytes through phagocytosis after MI [ 18 ]. However, DAMPs and ischemia triggered an excessive inflammatory response of infiltrative inflammatory cells, leading to increased myocardial damage.…”
Section: Discussionmentioning
confidence: 99%
“…These and related approaches to in vitro cardiac tissue engineering integrate biochemical, biophysical, and electromechanical stimuli to develop physiologically relevant systems for basic discovery and therapeutic benefit [ 67 69 ]. While cardiac MPSs confer the potential to study specific aspects of immune cell function in an appropriate dynamic environment, such as by incorporation of tissue resident MF, these applications have yet to be widely explored [ 70 ]. Such models are, however, emerging as a means of understanding and screening for cardiotoxicity in the post-MI environment [ 71 ].…”
Section: Experimental Models and Assessment Of Inflammatory Pathophys...mentioning
confidence: 99%
“…Bailey et al developed EHTs containing hPSC-CMs, 5% CFs, and 10% monocyte-derived macrophages, and showed that infection with SARS-CoV-2 induced typical features of myocarditis, including CM death, cardiac dysfunction, and impaired immune cell activation ( Bailey et al, 2021 ). Macrophages in engineered constructs have been shown to serve not only in immunological responses but also in tissue maturation, repair, regeneration, and vascularization ( Suku et al, 2021 ). Mills et al demonstrated that proinflammatory factors drive systolic and diastolic cardiac dysfunction in hPSC-CM-derived COs containing 20% ECs, recapitulating SARS-CoV-2 infection ( Mills et al, 2021 ).…”
Section: The Optimization and Sophistication Of 3d Cardiac Tissues Mo...mentioning
confidence: 99%